2017
DOI: 10.14393/bj-v33n5a2017-37311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modifying concentrations of calcium and magnesium on in vitro development of banana CV. Prata-Anã (Genomic group AAB)

Abstract: ABSTRACT:Research suggests that the development of micropropagated banana plants can be improved by altering nutrient concentrations in the culture medium. The aim of this study was to evaluate the in vitro development of banana plants exposed to varying concentrations of calcium and magnesium sulfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The positive effect of Mg on root development has been reported in many studies, e.g., higher root and shoot biomass were observed in banana grown under an increased concentration of Mg (370 mg L −1 of MgSO 4 ) in comparison to a lower concentration in the growth medium (185 mg L −1 of MgSO 4 ) (Rodrigues et al, 2017 ). A similar observation was reported by Chen et al ( 2017 ), who found that a higher Mg supply significantly improved root and shoot biomass and N and P uptake in soybean through the improved symbiotic performance of arbuscular mycorrhizal fungi (AMF) and rhizobia, both of which showed statistically significant positive correlations with the growth of the root system.…”
Section: Discussionmentioning
confidence: 79%
“…The positive effect of Mg on root development has been reported in many studies, e.g., higher root and shoot biomass were observed in banana grown under an increased concentration of Mg (370 mg L −1 of MgSO 4 ) in comparison to a lower concentration in the growth medium (185 mg L −1 of MgSO 4 ) (Rodrigues et al, 2017 ). A similar observation was reported by Chen et al ( 2017 ), who found that a higher Mg supply significantly improved root and shoot biomass and N and P uptake in soybean through the improved symbiotic performance of arbuscular mycorrhizal fungi (AMF) and rhizobia, both of which showed statistically significant positive correlations with the growth of the root system.…”
Section: Discussionmentioning
confidence: 79%